2015
DOI: 10.11113/jt.v76.5851
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Utilization of Coconut Shell and Coconut Fiber in Road Construction

Abstract: This paper provides a review of utilization coconut shell and coconut fiber in road construction. Coconut shell and coconut fiber are new waste materials used in highway industry. Some studies showed that coconut fiber can increase the stability, skid resistance and resilient modulus while coconut shell can improve the indirect tensile strength and static creep behavior of the modified asphalt pavement. In contrast, coconut fiber does not improve the fatigue life of the modified bituminous mixes. In general, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…To reach a homogeneous distribution of peat fibers in the asphalt mix, mixing should be performed only by the second approach; with the first approach, this homogeneity cannot be reached (see Figure 16). This is remarkable, since, considering the type and length of fibers, it has been reported in the literature that dry mixing was supposed to be sufficient [4,9,15,26] or it was not mentioned at all how fibers were mixed in the asphalt mixes [5][6][7][8]11,16]. It was mentioned by Kumar et al [15] that natural fibers tend to mix thoroughly with dry heated aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…To reach a homogeneous distribution of peat fibers in the asphalt mix, mixing should be performed only by the second approach; with the first approach, this homogeneity cannot be reached (see Figure 16). This is remarkable, since, considering the type and length of fibers, it has been reported in the literature that dry mixing was supposed to be sufficient [4,9,15,26] or it was not mentioned at all how fibers were mixed in the asphalt mixes [5][6][7][8]11,16]. It was mentioned by Kumar et al [15] that natural fibers tend to mix thoroughly with dry heated aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Se debe realizar una investigación detallada sobre los mecanismos de refuerzo similares de las fibras y cáscaras de cocos, así pues lo manifiestan Lay Ting, T., Putra Jaya, R., Abdul Hassan, N., Yaacob, H., & Sri Jayanti, D. (2015), indican además que las diversas propiedades de estos componentes del coco deben centrarse en el pavimento asfáltico investigaciones futuras, entonces por lo expuesto la presente investigación si podría ser aplicable en el Perú salvo con los ajustes de los porcentajes sobre todo de la fibra de coco y además considerando que el proceso de mezcla cumplan los requerimientos exigidos por el MTC y la normas ASTM.…”
Section: Discussionunclassified
“…176-190 -ISSN: 2313-1926 por lo que los agregados se recubrirán con una película más gruesa. En ese sentido también Lay Ting, T., Putra Jaya, R., Abdul Hassan, N., Yaacob, H., & Sri Jayanti, D. (2015) indican que esto puede reducir la oxidación de las mezclas asfálticas, la penetración y separación de la humedad, sin embargo para Al-Hadidy, A., & Yi-Qiu, T. (2009) todas las aplicaciones de asfalto tienen un problema, se volverá quebradizo a bajas temperaturas y blando a altas temperaturas, en ese sentido puede ser conveniente el uso de la cáscara y la fibra de coco pudiendo aumentar el rango de temperatura del asfalto y así cumplir con las exigencias técnicas de una mezcla asfáltica en caliente y además esta función puede reducir el secado y el agrietamiento que se producen en el pavimento asfáltico convencional cuando se enfrenta sobre todo a diversos climas a lo largo y ancho de nuestro país.…”
Section: Introductionunclassified
“…These micropores provide superb conditions for absorption to occur. Previous studies [11][12][13] concluded that CS has a low ash content. Ash is a non-carbon or mineral additive that does not combine chemically with carbon or mineral surface.…”
Section: Introductionmentioning
confidence: 99%